Reading Difficulty Viewed from Its Indicators in the Junior High School - Wigraha, Ketut Agung Devara (Universitas Pendidikan Ganesha, 2022)
This research aimed to analyze students' reading difficulties in understanding the descriptive text. This research applied descriptive qualitative research. The objects in this research were students' difficulties in the learning process in reading instruction of descriptive text, especially in finding the main idea or central theme, locating specific information, determining textual reference, and getting the meaning of a word or phrase. Students' sources of difficulties derived from the preliminary test results in understanding different descriptive texts, especially the main idea or central theme, specific information, textual reference, and word or phrase referential meaning of descriptive texts of a person, an animal, and a procedure. The subjects of this research were the seven grade students, consisting of 22 students in a class, and documents of students' test results were from difficulties in understanding descriptive texts of a person, an animal, and a procedure. The data were collected in the forms of primary and secondary data. The instruments used by the researcher to collect the data were the researcher as the main instrument, a non-objective test or short answer test consisting of 30 short answer questions related to descriptive texts of a person, an animal, and a procedure, and a focused group interview guide. The obtained data were analyzed descriptively. The results of this research show that students had difficulties in reading three descriptive texts based on reading indicators such as deducing the main idea or central theme, locating specific information, textual reference, and getting a word or phrase meaning. The sources of reading difficulties were identified by the researcher in an interview session with 5 representative students, namely having a limited vocabulary, lack of reading interest, lack of background knowledge or absence of knowledge, and the complexity of words or sentences in the text.